1992
DOI: 10.1136/sti.68.6.361
|View full text |Cite
|
Sign up to set email alerts
|

The value of urine specimens in screening for male urethritis and its microbial aetiologies in Tanzania.

Abstract: Objective-To evaluate the first void urine (FVU) specimen in screening for urethritis and its microbial aetiologies in a male African population in which urinary schistosomiasis is also prevalent. Of 18 subjects in all groups with urinary schistosomiasis nine had a positive LE test (50%), although three of these also had gonorrhoea. Chlamydial antigen was detected in the FVU specimen of all six subjects in whom it was detected in a urethral swab, and in an additional three subjects in the outpatient group. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…10 Mayaud et al 30 and Sellors et al 12 reported that the cost per case detected using LET dipstick to pre-screen urine specimens was relatively inexpensive compared with the strategy that would test every urine specimen with a diagnostic test. However, as Bowden observed, the social and economic costs of the sequelae of untreated STIs such as infertility are high with the hospital treatment of one case possibly outweighing those saved by screening with LET before definitive testing.…”
Section: Discussionmentioning
confidence: 99%
“…10 Mayaud et al 30 and Sellors et al 12 reported that the cost per case detected using LET dipstick to pre-screen urine specimens was relatively inexpensive compared with the strategy that would test every urine specimen with a diagnostic test. However, as Bowden observed, the social and economic costs of the sequelae of untreated STIs such as infertility are high with the hospital treatment of one case possibly outweighing those saved by screening with LET before definitive testing.…”
Section: Discussionmentioning
confidence: 99%
“…We previously evaluated this test in 151 medical outpatients without urethral discharge at a Mwanza hospital17 and found that 22 (15%) had a positive result. Of these, seven were found to have N gonorrhoeae or C trachomatis infection, or both, giving a positive predictive value of 32% in this outpatient group, similar to the 27% recorded in the general population in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies of the aetiology of urethritis in sub-Saharan Africa have usually focused on chlamydial and gonococcal urethritis. [6][7][8] There is little information on the prevalence of Trichomonas vaginalis infection in men in this region although trichomoniasis is known to be one of the most prevalent STDs in women, 9 10 and in one study trichomoniasis was associated with an increased risk of HIV transmission. 3 In male Kenyan transport workers trichomoniasis was more prevalent than either gonococcal or chlamydia urethritis (6.0% v 3.4% and 3.6% respectively) and 83% of T vaginalis infections were asymptomatic.…”
Section: Introductionmentioning
confidence: 99%